2012
DOI: 10.1128/aem.01658-12
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which Ambient Humidity May Affect Viruses in Aerosols

Abstract: ABSTRACTMany airborne viruses have been shown to be sensitive to ambient humidity, yet the mechanisms responsible for this phenomenon remain elusive. We review multiple hypotheses, including water activity, surface inactivation, and salt toxicity, that may account for the association between humidity and viability of viruses in aerosols. We assess the evidence and limitations for each hypothesis based on findings from virology, aerosol science, chemistry, and physics. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
217
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(228 citation statements)
references
References 62 publications
(93 reference statements)
7
217
0
4
Order By: Relevance
“…A lower fraction of IFVs are inactivated in the VIVAS compared with the BioSampler due to a much lower flow rate at each nozzle of the VIVAS (6.86 L/min distributed over 32 nozzles vs. 6.86 L/min over 3 nozzles). The sudden rehydration of IFVs, as occurs in an impinger, can also affect their viability (Yang and Marr 2012). The gradual rehydration in the VIVAS may serve to better maintain the viability of IFVs.…”
Section: Resultsmentioning
confidence: 99%
“…A lower fraction of IFVs are inactivated in the VIVAS compared with the BioSampler due to a much lower flow rate at each nozzle of the VIVAS (6.86 L/min distributed over 32 nozzles vs. 6.86 L/min over 3 nozzles). The sudden rehydration of IFVs, as occurs in an impinger, can also affect their viability (Yang and Marr 2012). The gradual rehydration in the VIVAS may serve to better maintain the viability of IFVs.…”
Section: Resultsmentioning
confidence: 99%
“…32 Generally, enveloped viruses survive better at lower RH, but there are many exceptions. 28 Other factors that affect aerosol activation in relation to RH include evaporative activity (ie, dehydration, rehydration), surface areas of particles, and pH. 28…”
Section: Environmental Factors That Influence Airborne Microbial Survmentioning
confidence: 99%
“…Temperature can affect microscopically by altering the structure of viral proteins (including proteins that are involved in viral entry and replication) and genome, and could also affect macroscopically by setting up large exchange air flows in space due to temperature difference (Tang, 2009). The influence of humidity on virus survival is mainly related to whether the virus has lipid envelopes or not (Yang & Marr, 2012). But it is important to note that humidity and temperature can interact to affect the survival of viruses in aerosols, viruses decay rapidly in dry and hot environments, and only 4.7% survival over 60 min procedure (Pyankov Oleg, Bodnev Sergey, Pyankova Olga, & Agranovski Igor, 2017).…”
Section: Factors Affecting Airborne Transmission In Nosocomial Settingsmentioning
confidence: 99%
“…Studies have shown that infectivity of viral aerosols could be reduced by ultraviolet radiation (Jordan, 1961;McDevitt et al, 2012;Walker & Ko, 2007). Higher salt content in the viral aerosols could reduce viability of the viral particles (Yang & Marr, 2012), while organic materials (e.g. blood, feces, mucus and saliva) could buffer against extreme environmental stress on viral particles in aerosols (Tang, 2009).…”
Section: Factors Affecting Airborne Transmission In Nosocomial Settingsmentioning
confidence: 99%